Potential of Experience Tourism in Chon Buri, Rayong, Chanthaburi and Trat - Pleerux, Narong; Nakpathom, Parinya (Journal of Thai Hospitality and Tourism, 2020)
Experience tourism is a type of tourism that integrates the concept of “Creative Economic” to develop cultural resources with lifestyle. The characteristic of experience tourism is the participation between tourists and hosts with creative cultural activities to be the co-experience, impressive, and good memorial. The objectives of the research aim to survey and create the map to present the location and evaluate the potential of experience tourism destinations in Chon Buri, Rayong, Chanthaburi, and Trat. The result shows a total of 32 experience tourism destinations located in Chon Buri 5 destinations, Rayong 9 destinations, Chanthaburi 7 destinations, and Trat 11 destinations. They are classified into 3 groups of potential; 22 tourism destinations in high potential, 8 tourism destinations in moderate potential and 2 tourism destinations in low potential. The highest potential destinations are mostly found in Trat which has 9 destinations. For Chon Buri, Rayong, and Chantaburi; there are 4 destinations in each province. The highest score (54 scores) of experience tourism destinations are Ban Chamrung and Ban Namchiew Community, the low potential inexperience tourism destinations have 2 destinations which are Khao Khun-In Thai Herbal Agricultural Center (23 scores) and Chomview Horse Riding Club (21 scores). This result can be applied to plan the activities and develop experience tourism destinations.